The influence of college students' academic stressors on mental health during COVID-19: The mediating effect of social support, social well-being, and self-identity - Li, Peng; Yang, Jiaqi; Zhou, Zhao; Zhao, Zijing; Liu, Tour (Frontiers in Public Health, 2022)
COVID-19 caused harmful mental consequence to the public. And mental health problems were very common among college students during the outbreak of COVID-19. Academic stressors was the main stress for college students, and social support, social well-being and self-identity were widely known as protective factors for mental health. Therefore, the study aimed to investigate the influence of academic stressors on mental health and the mediating effect of social support, social well-being and self-identity among college students during the outbreak of COVID-19. With 900 college students as subjects, use the College students' academic stressors questionnaire, Social support questionnaire, Social well-being scale, Self-identity scale and Depression anxiety stress scales (DASS-21), the results showed that: (1) Academic stressors had significantly negative correlation with social support, social well-being and self-identity, while having significantly positive correlation with mental health; (2) Academic stressors could positively predict mental health; (3) This effect was mediated by social support, social well-being and self-identity; (4) Work stressor was an important stressor during COVID-19, and had the same role as academic stressors in the structural equation model. The results of current study suggested that adjusting the academic stressors or work stressor of college students, enhancing social support, could improve social well-being and self-identity, and might effectively protect their mental health under the COVID-19 pandemic environment.